Second harmonic generation form imaging to condensed matter phase - Ali Hussain Reshak (Penerbit Universiti Malaysia Perlis, 2013)
Non-linear optical techniques have been exploited to develop a new generation of optical microscopes with unprecedented capabilities. These new capabilities include the ability to use near-infrared (IR) light to induce absorption, and hence fluorescence, from fluorophores that absorb in the ultraviolet wavelength region. Other capabilities of non-linear microscopes include improved spatial and temporal resolution without the use of pinholes or slits for spatial filtering, improved signal strength, deeper penetration into thick, highly scattering tissues, and confinement of photobleaching to the focal volume. Nonlinear optical materials have received much attention in recent years. They form a large group of semiconducting and dielectric materials with diverse optical, electrical, and structural properties. Some of these materials appear to be promising candidates for solar-cells applications, light-emitting diodes, nonlinear optics, and optical frequency conversion applications in solid state based tunable laser systems